Predictors and Moderators of Educational Interventions to Increase the Likelihood of Potential Living Donors for Black Patients Awaiting Kidney Transplantation - Rodrigue, James R. (J Racial Ethn Health Disparities, 2016)
Our aim was to identify predictors and moderators of the effects of a House Calls (HC) educational intervention, relative to a Group-Based (GB) intervention and to Individual Counseling (IC), in a randomized controlled trial to increase the likelihood of having living donor (LD) evaluations initiated and live donor kidney transplantation (LDKT). Black adults wait-listed for kidney transplantation (N=152) were randomized into one of the three educational conditions. We examined demographic, clinical, psychosocial, and socio-contextual baseline characteristics as predictors and moderators of having a potential LD initiate evaluation. HC assignment (OR=(2.02)4.73(11.05), P=0.001), younger age (OR=(0.91)0.94(0.98), P=0.001), more willingness to discuss donation with others (OR=(1.08)1.37(1.75), P=0.01), and larger social network (OR=(1.01)1.09(1.18), P=0.04) were significant multivariable predictors of having ≥1 LD initiate evaluation. Age (P=0.03) and social network size (P=0.02) moderated the effect of HC relative to IC and GB, but not GB relative to IC, on LD evaluation initiation. Our findings suggest that HC is most effective for patients <60 years old and those with average or large social network size.